Breastfeeding Mothers’ Knowledge and Behaviors on Giving Exclusive Mothers’ Milk to 0-6 Months Old Infants - Aniceto da C. Pacheco; Levi Anatolia S.M. Exposto; Aurelia de Araujo (International Journal Labs, 2021)
The composition of breast milk is suitable for the needs of the baby and contains protective substances with the most content in Colustrum. The problems are the mothers’ lack of knowledge, the onslaught of formula milk promotion, lack of support from health workers, etc. The method in this study is a descriptive quantitative, croossectional approach. The population in this study was 120 Breastfeeding Mothers, the samples were 30 Breastfeeding Mothers, the technique was random sampling. Some techniques analyze correlation data with results the relationship between knowledge (X1), strong classification level, behavior (X2) sufficient classification level and breastfeeding (Y), strong classification level. Based on statistical calculations carried out that the mother's knowledge and behavior is related to exclusive breastfeeding in infants aged 0-6 months. This statement is seen in the statistical results that tcount> ttable 8.88> 3.35. From the results of the calculation above it turns out Fcount> Ftabel or 8.88> 3.35 then reject Ho and accept Ha means, there is a significant relationship of knowledge and behavior of the mother towards exclusive breastfeeding in infants aged 0-6 months. So, statistically prove that knowledge and behavior have a significant impact on exclusive breastfeeding in infants aged 0-6 months.